Human T Lymphotropic Virus Type I (HTLV‐I) Proviral Load in Cerebrospinal Fluid: A New Criterion for the Diagnosis of HTLV‐I–Associated Myelopathy/Tropical Spastic Paraparesis? - Agnès Lézin; Stéphane Olindo; Stéphanie Olière; Michel Varrin‐Doyer; Regine Marlin; Philippe Cabre; Didier Smadja; Raymond Césaire (2005)
Human T lymphotropic virus type I (HTLV-I)-associated myelopathy/tropical spastic paraparesis (HAM/TSP) is associated with accumulation of HTLV-I-infected T cells in the central nervous system (CNS). However, data on HTLV-I proviral load in the CNS at the asymptomatic stage are still lacking. We measured HTLV-I proviral load in cerebrospinal fluid (CSF) cells from 17 patients with HAM/TSP and 25 asymptomatic carriers. The percentage of HTLV-I-infected cells in CSF cells and the CSF cell : peripheral blood mononuclear cell HTLV-I proviral load ratio were always >10% and >1, respectively, in the patients with HAM/TSP but were always <10% and <1, respectively, in the asymptomatic carriers. We propose that determination of HTLV-I proviral load in CSF cells should be included as a new parameter for the diagnosis of HAM/TSP.